2009
DOI: 10.5993/ajhb.33.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as a Predictor of Self-rated Health

Abstract: Objective: To report on the relationship between self-rated health and obesity. Methods: Computerassisted telephone survey of 5001 randomly selected individuals aged 18 years and over residing in California and Texas. Results: Obese individuals have a 3-fold greater odds of reporting reduced health. After controlling for the effect of demographic factors, health care utilization, chronic disease, and lifestyle behaviors, this relationship persists (OR: 2.33; 95% CI: 1.7, 3.2). Conclusion: Results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 27 publications
9
48
0
1
Order By: Relevance
“…Previous research has shown that the link between SRH and mortality may be weaker for cardiovascular mortality than for cancer mortality or mortality from other causes 30. Second, we found that the obese individuals rated their health lower than individuals with normal weight, which is in line with studies on general populations 31. Previous studies have shown that obese persons may experience discrimination, stigmatisation and major limitations in daily life linked to their obesity 32 33.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research has shown that the link between SRH and mortality may be weaker for cardiovascular mortality than for cancer mortality or mortality from other causes 30. Second, we found that the obese individuals rated their health lower than individuals with normal weight, which is in line with studies on general populations 31. Previous studies have shown that obese persons may experience discrimination, stigmatisation and major limitations in daily life linked to their obesity 32 33.…”
Section: Discussionsupporting
confidence: 89%
“…Sleep quality, although differently assessed in various studies, seems to have an important relationship with feeling of fresh and attentive. These results are in agreement with previous studies [18][19][20] . BMI is another important indicator of health status.…”
Section: Discussionsupporting
confidence: 94%
“…Corroborando com os resultados encontrados, está bem consolidado na literatura 34 que o excesso de peso aumenta as chances de pior autoavaliação de saúde. A obesidade, além de aumentar o risco para outras doenças crônicas, pode causar baixa autoestima, além de incapacidade funcional, problemas psicológicos e de interação social 35 ; essas condições podem ter impactado negativamente na forma como os bancários com excesso de peso perceberam sua saúde.…”
Section: Resultsunclassified